2013
DOI: 10.1002/cmdc.201300287
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐Aided Design, Synthesis and Validation of 2‐Phenylquinazolinone Fragments as CDK9 Inhibitors with Anti‐HIV‐1 Tat‐Mediated Transcription Activity

Abstract: The activity of the cyclin‐dependent kinase 9 (CDK9) is critical for HIV‐1 Tat‐mediated transcription and represents a promising target for antiviral therapy. Here we present computational studies that, along with preliminary synthetic efforts, allowed us to identify and characterize a new class of nontoxic anti‐CDK9 chemotypes based on the 2‐phenylquinazolinone scaffold. Inhibition of CDK9 translated into the ability to interfere selectively with Tat‐mediated transactivation of the viral promoter and in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…All synthesized compounds were subsequently evaluated in vitro for antiproliferative activity against three human cancer cell lines (HeLa, HepG2, and A549) and HIV‐1 inhibition activity used as a readout of cellular activity. Then, compounds 2c and 3b with good antiproliferative activity against cancer cells and excellent HIV‐1 inhibition activity were selected for further cellular mechanism studies which included testing the induction of cell apoptosis, and checking the level of cleaved PARP (the mark of apoptosis), the phosphorylation level at Ser2 of RNAPII CTD, and the expression level of CDK9 …”
Section: Methodsmentioning
confidence: 99%
“…All synthesized compounds were subsequently evaluated in vitro for antiproliferative activity against three human cancer cell lines (HeLa, HepG2, and A549) and HIV‐1 inhibition activity used as a readout of cellular activity. Then, compounds 2c and 3b with good antiproliferative activity against cancer cells and excellent HIV‐1 inhibition activity were selected for further cellular mechanism studies which included testing the induction of cell apoptosis, and checking the level of cleaved PARP (the mark of apoptosis), the phosphorylation level at Ser2 of RNAPII CTD, and the expression level of CDK9 …”
Section: Methodsmentioning
confidence: 99%
“…CDK 9 is a cyclin-dependent kinase that has been linked to HIV-1 pathogenesis in numerous studies—the CDK9/cyclin T1 enzyme, especially, has been shown to play an important role in HIV-1 transcription [ 54 – 56 ]. Due to the central nature of CDK9/cyclin T1 in HIV-1 transcription, several studies have investigated CDK 9 as a potential drug target [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…67 Metal-catalyzed multi-component synthesis of DHQ derivatives was also reported. [68][69][70][71][72][73] Generally, the use of metals or Lewis acids as catalysts did not lead to great yields (<90%), except when I 2 is used under solvent-free conditions at 115 C 69 ( Table 3).…”
Section: Conventional Reaction Conditionsmentioning
confidence: 99%